Principal Component Analysis of Biometric Traits Explain the Body Weight of HF Crossbred Cattle - Patel, Ashwini J; Rank, Dharmsi N (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present research was carried out to define the biometric traits of HF Crossbred Cattle from Livestock Research Station, AAU, Anand; Sarsa Heifer Farm - Amul Dairy, Anand; Ode Semen Station - Amul Dairy, Anand. The biometric traits recorded on 506 HF Crossbred Cattle and those are body length (BL), height at wither (HW), height at hip (HH), heart girth (HG), chest depth (CD) and width of hip (WH), live body weight (BW) and age. All the data were grouped sex-wise. Principal component analyses of biometric traits revealed that out of six components, two principal components were extracted in female and male group. The identified two components in female group could explain 95.88% of cumulative variance. First component accounted for 69.20 % of the variation. It was represented by significant positive high loading of BL (0.893), HW (0.911), HH (0.908), HG (0.879), CD (0.867) and WH (0.842). The second component explained 26.68 % of total variance with high loading of age (0.915). Out of two principal components, one (PC1) provided a means of reduction in the number of biometric traits to be recorded in HF crossbred female. In HF crossbred male group, the identified two components could explain 97.57% of cumulative variance. First component accounted for 60.58 % of the variation. It was represented by significant positive high loading of BL (0.836), HW (0.865), HH (0.901), HG (0.768), CD (0.804) and WH (0.737). The second component explained 36.99 % of total variance with high loading of age (0.888). First component seemed to be explaining the maximum of general body conformation in HF crossbred male. The result suggests that principal component analysis (PCA) could be used in breeding programs with a drastic reduction in the number of biometric traits to be recorded to explain body conformation and in selection of elite animals.